Precision medicine at the molecular level: The promise of structure-based drug design / Dr. Siti Azma Jusoh@Yusof and Dr. Gurmeet Kaur Surindar Singh - Jusoh@Yusof, Siti Azma; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On July 11, 2023, Professor Dr. Habibah Wahab delivered a lecture titled "Precision Medicine at the Molecular Level: Exploring the Potential of Structure-Based Drug Design" at DK 10, FF4 Building, Faculty of Pharmacy, UiTM Puncak Alam. This lecture was a part of the collaborative teaching effort for the PHC 664-Structure-based Drug Design elective subject under the Bachelor of Pharmacy (PH240) programme, which was supported by the Centre for Innovative Delivery and Teaching Development, UiTM. The primary objective of this effort is to enhance students' learning experiences by providing them with industry insights and cutting-edge knowledge. Professor Dr. Habibah Wahab is widely recognised for her significant contributions in the field of computer-aided drug design in Malaysia. Her expertise is evident in her use of advanced computational techniques, including molecular dynamics simulations and virtual screening, to analyse the interaction between potential compounds and their target receptors. The insights gleaned from these computational findings are crucial in the decision-making processes pertaining to chemical compound synthesis and bioassay experiments. The application of such techniques has facilitated pharmaceutical companies in economising costs and reducing the duration required to bring drugs to market.